PENGARUH TRAINING, MOTIVASI DAN PEMBENTUKAN KARAKTER TERHADAP KINERJA KARYAWAN PERUSAHAAN PT. CATUR SENTOSA ADIPRANA, Tbk - Hilda; Susiani Dewi, Kadek Ayu; Lazuardi , Afried; Permana, Amipriyadi Gerha (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
Employees as a major resource companies must provide the best service to customers and provide optimum performance so that consumers feel underserved and satisfied. If consumers are not satisfied to make complaints that could damage the company's image. This indicates that the resource manusiasangat affect the success in achieving its objectives. Human resources has the function to manage what a company has to the maximum to obtain the expected results of the company.As a company engaged in the service PT.CaturSentosaAdiprana, Tbk facilitate employees by providing training that are expected to provide motivation and can form the character of employees that can improve performance. Employees who received training, there will be motivation in itself and with training can also form a character on an employeeor employees who can influence to improve the quality of performance. Performance is the result or the overall success rate of a person during a certain period in performing tasks compared to a variety of possibilities, such as the standard of the work